Rehabilitacija bolnikov z okvaro hrbtenjače zaradi raka - Škorjanc, Tatjana (Rehabilitacija (Ljubljana), 2008)
The article discusses the contents of rehabilitation programs for oncologic patients with spinal cord lesions. Apart from medical rehabilitation, the programs include psychosocial rehabilitation and when required also vocational rehabilitation. The article describes the most frequent complications resulting from spinal cord lesions and related necessary preventive measures.
Keywords: bolniki; hrbtenjača; medicinski pripomočki; okvare; rak (medicina); rehabilitacija